Innovation Networks as Elements of Regional Innovation System: State-of-Art Review; International Business Information Management Association Conference, IBIMA - Chistyakova N. O. Natalya Olegovna; Fedenkova A. S. Anna Sergeevna; Shabaldina N. V. Nataliya Vladimirovna; Abushakhmanova Yu. V. Yuliya Vyacheslavovna (2015, 2015)
Title screen